2019
DOI: 10.3390/toxins11090492
|View full text |Cite
|
Sign up to set email alerts
|

Gallic Acid Triggers Iron-Dependent Cell Death with Apoptotic, Ferroptotic, and Necroptotic Features

Abstract: Gallic acid (GA) is a natural anti-cancer compound that can be found in many food sources, including edible mushrooms, fruits, and vegetables. Studies generally attribute the anti-cancer activity of GA to the induction of apoptosis. Here, we reported that GA activated iron-dependent cell death mechanisms with apoptotic, ferroptotic, and necroptotic features. Our time-lapse live-cell microscopy study demonstrated that GA could induce coexistence of multiple types of cell death pathways, including apoptosis char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 45 publications
8
38
1
Order By: Relevance
“…A recent study by Tang and Cheung [45] demonstrated that GA could induce coexistence of multiple types of cell death pathways, including apoptosis characterized by mitochondrial cytochrome c release and caspase-3 activation, ferroptosis characterized by lipid peroxidation, and necroptosis characterized by the loss of plasma membrane integrity [45]. Our study is in consistent with their study that GA could have anticancer effect via different cell death mechanism and also we found that the cell death mechanisms of GA could be potentiate by using low-level laser irradiation as pre-treatment.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study by Tang and Cheung [45] demonstrated that GA could induce coexistence of multiple types of cell death pathways, including apoptosis characterized by mitochondrial cytochrome c release and caspase-3 activation, ferroptosis characterized by lipid peroxidation, and necroptosis characterized by the loss of plasma membrane integrity [45]. Our study is in consistent with their study that GA could have anticancer effect via different cell death mechanism and also we found that the cell death mechanisms of GA could be potentiate by using low-level laser irradiation as pre-treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Pyrogallol [188] and propyl gallate [189] can also reduce the content of GSH, promote the ROS production, and most probably become new inducers of ferroptosis. Tang and Cheung [190] showed that GA can activate iron-dependent cell death with apoptotic, ferroptotic, and necroptotic features. Their timelapse live-cell microscopy experiments demonstrated that GA could induce contemporarily different RCD types, including apoptosis with mitochondrial cytochrome c release and caspase-3 activation, ferroptosis with lipid peroxidation, and necroptosis with the loss of plasma membrane integrity.…”
Section: Polysaccharides As Ferroptosis Switchersmentioning
confidence: 99%
“…However, the main interest in GA and its derivatives surrounds its anticancer activity. Previous studies have revealed that GA effectively induces selective apoptosis in various cancer cells, including HeLa, HCT-15, SH-SY5Y, and NSCLC cells [16][17][18][19] and inhibits proliferation and migration via regulating fatty acid synthase in TSGH-8301 cells [20]. Recent studies also revealed potential anticancer effects of GA is due to its ability to inhibit cell proliferation and to induce apoptosis in vivo [21,22].…”
Section: Introductionmentioning
confidence: 99%